2017
DOI: 10.1111/1556-4029.13695
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance as a Technique for Estimating Postmortem Interval,,

Abstract: Estimation of postmortem interval (PMI) is a critical component of death investigation. A cadaver can be hypothesized to be a resistor-capacitor (RC) circuit the impedance (Z) of which changes in a quantifiable manner as the cadaver decomposes. This hypothesis was tested using bioelectrical impedance analysis (BIA) equipment to apply a current with a fixed amplitude at a single frequency to four cadavers over time and measuring two components of Z, resistance (R) and reactance (X ). Quadratic regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that there are six current circuits (arm-to-arm, right-arm–left-leg, right-arm–right-leg, left-arm–left-leg, right-arm–right-leg, foot-to-foot) for the equipotential-based OS-BIA technique [ 28 , 29 ]; however, these circuits are not clearly defined, especially for the determination of reactance and the phase angle. Importantly, studies have reported additional body current circuits, such as right-arm–right-leg, left-leg–right-leg circuits, and impedance parameters in these current circuits can overlap and lead to distorted results in impedance values [ 1 , 37 , 41 ]. This overlap of the current circuits could be eliminated by positioning the arm to be adducted 90 degrees at the shoulder joint, so that the voltage between the measured and unmeasured volage electrode is equipotential.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that there are six current circuits (arm-to-arm, right-arm–left-leg, right-arm–right-leg, left-arm–left-leg, right-arm–right-leg, foot-to-foot) for the equipotential-based OS-BIA technique [ 28 , 29 ]; however, these circuits are not clearly defined, especially for the determination of reactance and the phase angle. Importantly, studies have reported additional body current circuits, such as right-arm–right-leg, left-leg–right-leg circuits, and impedance parameters in these current circuits can overlap and lead to distorted results in impedance values [ 1 , 37 , 41 ]. This overlap of the current circuits could be eliminated by positioning the arm to be adducted 90 degrees at the shoulder joint, so that the voltage between the measured and unmeasured volage electrode is equipotential.…”
Section: Discussionmentioning
confidence: 99%
“…С другой стороны, следует отметить, что при наличии дисперсии Z в целом в исследуемом интервале частот (от 100 Гц до 100 кГц), непосредственно для высоких частот (10 и 100 кГц) дисперсия практически отсутствует, т. е. коэффициент поляризации k п близок к единице для всех сроков ДНС в любых условиях. Известно, что дисперсия Z для высоких частот присуща только живым тканям и отсутствует у мертвых [22]. Именно в интервале высоких частот от 10 до 1000 кГц для живых тканей дисперсия импеданса определяется поляризацией фосфолипидов мембран клеток в поле внешнего электрического тока и дипольной поляризацией структурных образований в цитоплазме.…”
Section: обсуждение интерпретация/научная значимостьunclassified